Determinants of Capital structure in Islamic and conventional Jordanian banks for the period 2003 to 2019 “comparative empirical study” - Al-Zayout, Moatasem; Al-Zayout, Montasir; Ibrahim, Dalia (Jordan Journal of Islamic Studies, 2023)
This study aimed to examine the determinants of capital structure in Jordanian Islamic and Conventional banks comparatively for the period 2003 to 2019 including the global financial crisis. The study examines the effect of each of the following: (dividends payout, profitability, capital adequacy ratio, bank size, liquidity and bank growth) on capital structure (measured by the financial leverage) where Stepwise Regression was applied. The results showed that Capital Adequacy ratio has been proved to be a determining factor of the capital structure in all models of the study, since this ratio is an indicator of the stability and efficiency of the bank. On other side, the bank size has a negative and significant effect on capital structure of the conventional bank. Moreover, the results presented a significantly negative effect of profitability on conventional bank capital structure, the more profit retained in bank's equity the less the need for liability, The study suggests urging the competent authorities to work to provide Islamic banks with the option of financing that is compatible with Islamic law, in order to achieve fairness in the competitive advantage between them and traditional banks and to increase the possibility of expanding their investment activities.